Sizing the Cannabis Market: A Demand-Side and User-Specific Approach in Seven European Countries - van Laar, Margriet; Frijns, Tom; Trautmann, Franz; Lombi, Linda (Current Drug Abuse Reviews, 2013)
Demand-based estimates of total cannabis consumption rarely consider differences among different user types and variation across countries. To describe cannabis consumption patterns and estimate annual consumption for different user types across EU Member States, a web survey in Bulgaria, Czech Republic, Italy, the Netherlands, Portugal, Sweden and United Kingdom (England & Wales) collected data on cannabis use patterns from 3,922 persons who had consumed cannabis at least once in the past year. They were classified into four groups based on their number of use days in the past 12 months: infrequent users or chippers (<11 days), occasional users (11-50 days), regular users (51-250 days) and intensive users (>250 days). User type specific data on typical amounts consumed were matched with data on numbers of users per user type estimated from existing population surveys, taking differences in mode of consumption, age and gender into account. Estimates were supplemented with data from populations of problem users to compensate for under coverage. Results showed remarkably consistent differences among user groups across countries. Both the average number of units consumed per typical use day and the average amount of cannabis consumed per unit increased across user types of increasing frequency of use. In all countries except Portugal, intensive users formed the smallest group of cannabis users but were responsible for the largest part of total annual cannabis consumption. Annual cannabis consumption varied across countries but confidence intervals were wide. Results are compared with previous estimates and discussed in the context of improving estimation methods.
Keywords: demand